2022
DOI: 10.1177/01976931221109301
|View full text |Cite
|
Sign up to set email alerts
|

Studying lithic microdebitage with a dynamic image particle analyzer

Abstract: Lithic microdebitage has great archaeological potential to elucidate ancient stone tool production. So far, archaeologists have collected soil samples, separated them into size fractions, and analyzed them manually under a microscope to identify microdebitage. This time- and labor-intensive process has limited the number of samples and introduced intra- and inter-observer errors. Here, we discuss lithic microdebitage analysis with a dynamic image particle analyzer. This machine takes videos of soil particles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Most of the variables measured are dependent on one another, and some even use the exact same measurements. Our investigations have revealed that transparency is overwhelmingly the most significant variable for differentiating between these two particle types (Eberl et al, 2022, this issue; Estrada Aguila et al, 2022, this issue; Johnson et al, 2021).…”
Section: Methods: Present Studymentioning
confidence: 83%
See 4 more Smart Citations
“…Most of the variables measured are dependent on one another, and some even use the exact same measurements. Our investigations have revealed that transparency is overwhelmingly the most significant variable for differentiating between these two particle types (Eberl et al, 2022, this issue; Estrada Aguila et al, 2022, this issue; Johnson et al, 2021).…”
Section: Methods: Present Studymentioning
confidence: 83%
“…DIA was conducted at Vanderbilt University using the PartAn 3D particle analyzer (see Eberl et al, 2022, this issue) (Figure 6). Each sample was individually poured into a funnel at the top of this analyzer and then passed through a vibrating tray until each particle was dropped individually into the measurement area (Figure 7).…”
Section: Methods: Present Studymentioning
confidence: 99%
See 3 more Smart Citations